2022
DOI: 10.3389/fnagi.2022.934921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hearing loss on cognitive function in patients with mild cognitive impairment: A prospective, randomized, and controlled study

Abstract: BackgroundHearing loss (HL) may increase the risk of cognitive decline in the elderly. However, the randomized controlled study on the effect of HL on cognitive function in mild cognitive impairment (MCI) is very limited.MethodsFrom 1 November 2020 to 30 March 2022, 1,987 individuals aged 55–65 years were randomly divided into the MCI with hearing impairment (MCI-HI), MCI without HI (MCI-nHI), and no MCI (nMCI) groups by stratified sampling, with 30 participants in each group. The Mini-Mental State Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…depression, history of stroke and orthostatic hypotension, diabetes) that are consistently associated with dementia, which should be further explored when developing a dementia risk prediction tool for primary care for PCPs to implement early interventions to slow the progression of dementia Predictors were selected for a dementia risk prediction tool; the tool was not developed [ 41 ] Cognitive decline in MCI Dementia risk prediction metrics This randomized clinical trial (RCT) conducted in China with a cohort of individuals aged 55–65 found that right-sided hearing loss may be a predictor of cognitive decline in older adults. This morbidity can be utilized as a marker to support PCPs in identifying high-risk individuals for early prevention of cognitive decline Risk predictor suggested; the tool was not developed [ 42 ] Dementia Dementia risk prediction metrics This observational study conducted in Portugal identified gastrointestinal diseases as potential risk factors when screening for dementia in a younger cohort aged 50 and older, which could be readily implemented in primary care. However, gastrointestinal diseases are only demonstrated to be highly correlated with dementia risk when used in a multivariate model with other factors such as gender, age, APOE ε4 allele, female gender, and low education, and needs to be further validated Risk predictor suggested; the tool was not developed [ 43 ] Dementia MyHealthNetwork MyHealthNetwork is a digital health tool to monitor brain health to lower dementia risk, especially given the positive association between hypertension and the risk of future dementia.…”
Section: Resultsmentioning
confidence: 99%
“…depression, history of stroke and orthostatic hypotension, diabetes) that are consistently associated with dementia, which should be further explored when developing a dementia risk prediction tool for primary care for PCPs to implement early interventions to slow the progression of dementia Predictors were selected for a dementia risk prediction tool; the tool was not developed [ 41 ] Cognitive decline in MCI Dementia risk prediction metrics This randomized clinical trial (RCT) conducted in China with a cohort of individuals aged 55–65 found that right-sided hearing loss may be a predictor of cognitive decline in older adults. This morbidity can be utilized as a marker to support PCPs in identifying high-risk individuals for early prevention of cognitive decline Risk predictor suggested; the tool was not developed [ 42 ] Dementia Dementia risk prediction metrics This observational study conducted in Portugal identified gastrointestinal diseases as potential risk factors when screening for dementia in a younger cohort aged 50 and older, which could be readily implemented in primary care. However, gastrointestinal diseases are only demonstrated to be highly correlated with dementia risk when used in a multivariate model with other factors such as gender, age, APOE ε4 allele, female gender, and low education, and needs to be further validated Risk predictor suggested; the tool was not developed [ 43 ] Dementia MyHealthNetwork MyHealthNetwork is a digital health tool to monitor brain health to lower dementia risk, especially given the positive association between hypertension and the risk of future dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Although causal relationships are incompletely understood, MAs and SRs demonstrate a clear association between ARHL and cognitive loss. [196][197][198][199][200] ARHL worsens cognitive decline in those with mild cognitive impairment 201 and HL is worse in those with cognitive impairment, specifically Alzheimer's. 196 Most cognitive domains, regardless of each domain's reliance on auditory function, are impaired by hearing loss, including executive function, processing speed, working memory, language, verbal memory, and general cognition.…”
Section: Cognitionmentioning
confidence: 99%